PENERAPAN MODEL PEMBELAJARAN PICTURE AND PICTURE UNTUK MENINGKATKAN KEMAMPUAN BERBICARA ANAK TK LABORATORIUM UNDIKSHA SINGARAJA - Mila Puspita, Putu; Gading, I Ketut (Universitas Pendidikan Ganesha, 2018)
This research was aimed at investigating the improvement of children speaking skill by using picture and picture learning model. This research was classroom action research which was conducted in two cycles. The subjects of this research were B1 group in one semester in Laboratorium Undiksha Kindergarten Singaraja 2018/2019 academic year with number 26 children consisted of 12 male children and 14 female children. The data of the children speaking skill was obtained through observational method by using observation sheet instrument. The obtained data was analyzed by utilizing descriptive statistical analysis method and quantitative analysis method. The analysis result showed that in the first cycle was 67,91% at average category then increased in the second cycle into 82,33% at high category. Thus, there was improvement by the implementation of picture and picture learning model could improve the children speaking skill at B1 group in the one semester in Laboratorium Undiksha kindergarten Singaraja 2018/2019 academic year. Keyword: picture and picture learning model, speaking skill